2007
DOI: 10.1007/s11482-007-9030-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work/Family Conflict on Intention to Quit: The Mediating Roles of Job and Life Satisfaction

Abstract: Research has shown consistently that job satisfaction predicts turnover, but much less attention has been given to the how relationships between work and nonwork or how overall subjective evaluations of life (i.e., life satisfaction) affects turnover. We tested a model that included job satisfaction, life satisfaction, and conflict between work and nonwork domains of life as predictors of intent to quit. Results from a sample of Air Force personnel revealed that life satisfaction was a significant predictor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 65 publications
6
52
0
2
Order By: Relevance
“…Previous research on the relationships between family-work confl ict and job satisfaction showed inconclusive results. Similarly to our results, some studies showed that confl ict between work and family life had negative effect on job satisfaction (Adams et al 1996, Rode et al, 2007, but also that it has very little or no effect on job or life satisfaction (Wallace et al, 2007). Taking into account that our sample consisted of healthcare professionals and mostly women, it could be expected that they lead an unbalanced life, working shifts and having family responsibilities, which signifi cantly infl uenced their job satisfaction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous research on the relationships between family-work confl ict and job satisfaction showed inconclusive results. Similarly to our results, some studies showed that confl ict between work and family life had negative effect on job satisfaction (Adams et al 1996, Rode et al, 2007, but also that it has very little or no effect on job or life satisfaction (Wallace et al, 2007). Taking into account that our sample consisted of healthcare professionals and mostly women, it could be expected that they lead an unbalanced life, working shifts and having family responsibilities, which signifi cantly infl uenced their job satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…Off-the-job activities and confl ict between work and family life were found to be good predictors of life and job satisfaction (Rode, 2004;Rode et al, 2007), as well as quality of life in general (Greenhouse et al, 2003). People reporting high levels of work-family imbalance were found to be less satisfi ed with their job and life, spending more time on work than on family was related to lower quality of life experienced.…”
Section: Off-the-job Activities and Well-being In Healthcare Professimentioning
confidence: 99%
“…In these cases, stress is likely to lead to increased leaving intention. In the same vein, work-family conflict dampens employee job satisfaction and affective commitment (Rode, Rehg, Near, & Underhill, 2007). This paper suggests a complementary account of how work-family conflict may lead to employee turnover, drawing on the Job Embeddedness Theory.…”
Section: Introductionmentioning
confidence: 94%
“…In particular, the results of some studies reveal that, on the one hand, there seems to be a link between formal instruments, such as the availability of benefits to support family needs, with informal organizational factors, such as the organizational culture, the support of the management and the amount of autonomy that employees enjoy (Allen, 2001;Anderson et al, 2002;Behson, 2002Behson, , 2005.On the other hand, indexes measuring the personnel's morale, commitment, production, absenteeism, and turnaround, demonstrate that there exist economic benefits that derive from the implementation of work-family balance instruments. Among the benefits one can enumerate (Bevan et al, 1999): the increase in: assistance for illness (Rode et al, 2002); in employees' pay and productivity; in the length of employment (loyalty); and in the effectiveness of THE 6TH INTERNATIONAL CONFERENCE "THE CHANGING ECONOMIC LANDSCAPE: ISSUES, IMPLICATIONS AND POLICY OPTIONS" personnel selection and hiring procedures.…”
Section: Csr and Corporate Family Responsibilitymentioning
confidence: 99%